Application of scalable and inexpensive modification on carbon in clean technologies - Hossain, Md Zawad (Kansas State University, 2024)
Carbon can be a game-changing material to meet the global challenges in freshwater production and renewable conversion and storage devices due to their versatile nature. However, its hydrophobic characteristics, poor stability, low electrical conductivity, and small number of active sites limit its functions. Therefore, numerous efforts have been made to develop modified carbon materials to enhance their properties as electrocatalysts and electrode materials. This research focuses on developing modified nanocarbon materials for applications in water desalination by capacitive deionization (CDI) and electrochemical H₂O₂ synthesis via oxygen reduction reaction (ORR). In the first application, a systematic study has been conducted for controllable and quantifiable impregnation of a cationic surfactant cetyl trimethyl ammonium bromide (CTAB) and an anionic surfactant sodium dodecyl sulfate (SDS) on activated carbon (AC) electrodes, respectively, and used to construct a asymmetric electrochemical cells. The electrochemical properties have been thoroughly characterized with cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) measurements. The electrochemical cells consisting of a pair of such electrodes are then studied for CDI by flow of 1000 ppm NaCl solution between the two electrodes, i.e., in the flow-by configuration. Three different CDI modes have been investigated, including normal CDI (applying a voltage waveform with positive voltage bias at the CTAB-modified AC electrode for charge and zero voltage for discharge), inverted CDI (applying a reverse voltage waveform from the normal CDI), and bipolar CDI (applying a positive voltage bias on CTAB-modified AC electrode for a period and the reversed voltage in the following period). The electrochemical and normal CDI studies have shown that the increase of surfactant loadings reduces the electrochemical double layer capacitance and salt adsorption capacity. However, the CDI stability and charge efficiency are enhanced. The energy consumption is lower for surfactant-modified AC electrodes. The inverted CDI has demonstrated the effectiveness of surfactant modification as a charge-selective membrane. The bipolar CDI has demonstrated an enhanced salt adsorption capacity with surfactant-modified AC electrodes and the improved stability against carbon oxidation. In the second application, a preliminary study was conducted on developing electrocatalysts for ORR via N-doped carbon. A new type of graphitic carbon with a unique structure (crumbled balls with turbostratic multi-layer graphene sheets) produced by a high-temperature gas detonation process is explored for N-doping via a post-growth thermal annealing process. From the linear sweep voltammetry in O₂-saturated 0.50 M H₂SO₄ solution by rotating disk electrode (RDE), it has been demonstrated that, after N-doping on the carbon, the onset potential of ORR is increased by +317 mV and half-wave potential is improved by +270 mV compared to the pristine graphitic carbon. The study by rotating ring disk electrode (RRDE) further demonstrates that N-doped graphitic carbon exhibits a 2e⁻ ORR mechanism with a high H₂O₂ selectivity of ~60%. With further optimization, this could be a good candidate for selective H₂O₂ production by electrolysis.
Keywords: Capacitive deionization; Oxygen reduction reaction